The Roles of Fibroblast Growth Factor (FGF)-23, α-Klotho and Furin Protease in Calcium and Phosphate Homeostasis : A Mini-Review - Mattoo, Roshan L. (Indian journal of clinical biochemistry, 2014)
The roles of calcitonin, parathormone and calcitriol in the regulation of plasma calcium and phosphate are well-established. However, in autosomal-dominant hypophosphatemic rickety patients, studies have revealed normal plasma levels of calcium, associated with normal thyroid and parathyroid functions, but decreased levels of phosphate and calcitriol despite adequate reserves of vitamin D. Also, in tumoral calcinosis, persistent hyperphosphatemia with increased levels of 1,25(OH) 2 D 3 have been observed. These studies indicate the involvement of factors other than the ones already known. The first decade of this century/millennium has led to the discovery of the involvement of fibroblast growth factor-23, furin protease and α-klotho in the homeostasis of calcium and phosphate, which is the subject of this mini-review.